高屏區國民小學組織文化特性與行政決策運作關係之研究 A Study of the Relationship between Characteristics of Organization Culture and Operation of Administrative Decision-Making in the Elementary School in Kaohsiung and Pingtung - 吳旻珊 Wu, Min-Shan; 吳宗立 Wu, Tsung-Li (National Changhua University of Education, 2008)
本研究旨在探討高屏區國民小學組織文化特性與行政決策運作之關係。為達研究目的乃以高雄縣、高雄市、屏東縣國民小學569 位學校成員為研究對象，兼採文獻分析及問卷調查法，以「國民小學組織文化特性與行政決策運作問卷」為工具進行研究。經由平均數、標準差、t 檢定、單因子變異數分析、Pearson 積差相關與逐 步多元迴歸之分析結果，獲得之研究結論如下： 一、國民小學組織文化中以科層性表現較明顯，對於行政決策運作則較重視執行活動。 二、男性、都市學校、資深的學校教師較能感受到科層性文化；偏遠地區的學校教師在凝聚性文化與回饋行動上的知覺較強。 三、男性、資深、小規模學校的教師較積極投入行政決策運作。 四、國民小學教師對組織文化特性的知覺越強，在行政決策運作的表現也越積極；尤其是專業性與凝聚性文化對行政決策運作具有相當的影響力。最後，根據研究結論，提出相關建議作為教育行政機關、學校經營之參考。 The main purpose of this study is aimed to investigate the relationship between characteristics of organization culture and operation of administrative decision-making in the elementary school. In order to realize the purpose above, literature view, document analysis, and survey selected. A sample of 569 faculty of public elementary school in Kaohsiung City, Kaohsiung County, and Pingtung County was selected. By means of several statistical methods, such as mean, standard deviation, t-test, one-way ANOVA, Pearson product-moment correlation and multiple stepwise regression analysis, the results of presented as follows: 1. The bureaucratic culture is the most significant among organization cultures in the elementary school. For the administrative decision-making, it puts more emphasis on the executive action. 2. The faculty who are male, senior, and in the metropolitan schools show higher perception of the bureaucratic culture and the agglomerate culture, while faculty in the suburban schools show the highest perception of the agglomerate culture and feedback action. 3. The faculty who are male, senior, and in the smaller schools more voluntarily participatein the operation of administrative decision-making. 4. The higher the faculty's awareness of the characteristics of organization culture, the more efficient the effects of the operation of administrative decision-making. The professional culture and the agglomerate culture absolutely aid the prediction to the operation of administrative decision-making. According to the results of this study, some suggestions are proposed for the educational administrative agencies, the elementary schools' faculty, and future study.